Pelatihan Pembuatan Komposter untuk Penanganan Limbah Hasil Perkebunan di Desa Karang Sidemen, Kecamatan Batukliang Kabupaten Lombok Tengah - Priyati, Asih; De Side, Gagassage Nanaluih; Sumarsono, Joko; Abdullah, Sirajuddin Haji; Dewi, Endang Purnama; Amaliah, Wenny; Putra, Guyup Mahardhian Dwi (Universitas Mataram, 2024)
Karang Sidemen Village is one of the villages in North Batukliang Subdistrict, Central Lombok Regency which is adjacent to the forest area and the foot of Mount Rinjani causing adequate water sources with the majority of the population as farmers and planters. The natural conditions and life in Karang Sidemen village which is dominated by agriculture is very supportive of the fulfillment of the needs of cultivation production facilities in the form of compost will be very profitable if it can be provided from the processing of agricultural organic waste. The existence of abundant agricultural waste from various agricultural products has a very good potential to meet the needs of compost that will support the cultivation process, namely to support plant growth. Therefore, one of the alternative solutions that can be offered for handling organic waste in Karang Sidemen Village is by processing waste into compost which can be applied as a soil fertilizer. In this community service activity, training will be conducted on making composter tools for handling organic waste in the Karang Sidemen Village community. The community is given socialization and training on how to make an organic composting device or composter with tools and materials that are easily obtained so that the community is able to make their own composter easily, and can utilize organic waste as soil fertilizer. With this composter making training, it is hoped that the community will find it easier to compost organic materials that are easily obtained in their environment, so as to reduce the hoarding of organic waste generated by the community, and can support the Agrotourism village program to the fullest. In addition, by being able to provide compost independently, the community can further reduce their agricultural production costs so as to increase community welfare and income.